Skull-facial anthropometric traits of forensic odontologic interest for estimating sex, race, and age. Review of the literature - Castillo-Páez, José Alberto (2021)
One of the main functions of anthropologists and forensic dentists is to identify subjects according to physical characteristics of the features presented using non-routine methods. These characteristics, especially bone, allow professional to determine the sex, age and racial origin of the remains or skeleton found. Dentists focus on features belonging to the stomatognathic system, while anthropologists study the bones that make up the human body. In this study, we describe the investigations of cranio-facial anthropometric features of dental interest carried out by anthropologists to identify the sex, race, and age of skeletal remains or skeletons. in addition, we describe the so-called dental anthropology that studies the elements of the stomatognathic system from an anthropological point of view. Electronic literature was reviewed through search engines such as PUBMED, Google Academic and SciELO with the search terms “Forensic Dentistry, Forensic Anthropology, Sex Determination, Ancestry Determination and Age Determination”. Knowledge of the craniofacial anthropological features from the forensic point of view is of great importance in individualized and multidisciplinary studies by forensic dentists and anthropologists in the identification of skeletal remains.